The Book ofThe Universe: Its Place and Development in Bediuzzaman’s Thought - Sükran Vahide (TSAQAFAH, 2014)
Bediuzzaman Said Nursi is one of Modern Muslim scholar who successfully synchronized between al-Qur’an and science. In one of his writing, “Risale-i Nur”Nursi presented what called by “The Book of Universe”. Writer found that Nursi’s argumentation built on his representation upon this universe as reading object –Book of Universe- , then to reach the complete understanding toward this ‘book’ is not another than full reflective thought (tefekkür) as a scientific progress to achieve knowledge truth compatible with al-Qur’an. Tefekkür built on unity of rational intellect and Sufism way of heart purity to create this “reading” process toward universe as a spiritual-scientific point of view. Human knowledge that synergistic between the Qur’an and the universe will deliver to the purpose of human existence is that he should recognize Him. Finally, writer conclude that Risale-i Nur is a new methodology in al-Qur’an development based on rational, logic and reflective thought system in the metaphorical word; “Book”, that is worth the idealism as a offer of modern perspective to criticize Western science and philosophy which often role negatively to Islamic Studies.